2006
DOI: 10.2527/jas.2006-156
|View full text |Cite
|
Sign up to set email alerts
|

BOARD-INVITED REVIEW: Intrauterine growth retardation: Implications for the animal sciences1

Abstract: Intrauterine growth retardation (IUGR), defined as impaired growth and development of the mammalian embryo/fetus or its organs during pregnancy, is a major concern in domestic animal production. Fetal growth restriction reduces neonatal survival, has a permanent stunting effect on postnatal growth and the efficiency of feed/forage utilization in offspring, negatively affects whole body composition and meat quality, and impairs long-term health and athletic performance. Knowledge of the underlying mechanisms ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
889
4
27

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 983 publications
(942 citation statements)
references
References 180 publications
(325 reference statements)
22
889
4
27
Order By: Relevance
“…Alternatively, the practice of flushing before and during the breeding season can result in overfeeding [50]. Such nutrient imbalance has been shown to severely impair fetal and placental development [50]. Interestingly, we found most of the disturbed gene expression were located in the KCNQ1 and IGF2/H19 clusters, consistent with the role of IGF2 as a major fetal growth regulator [54].…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Alternatively, the practice of flushing before and during the breeding season can result in overfeeding [50]. Such nutrient imbalance has been shown to severely impair fetal and placental development [50]. Interestingly, we found most of the disturbed gene expression were located in the KCNQ1 and IGF2/H19 clusters, consistent with the role of IGF2 as a major fetal growth regulator [54].…”
Section: Discussionsupporting
confidence: 65%
“…Maternal stressors induce changes in expression of the fetal genome, which can permanently alter the offspring’s physiology, development, metabolism, and growth [50], as reported in mice and rats [51,52]. Understanding the effect of poor maternal nutrition in ovine fetal development is not only relevant to agriculture [53], but also to modeling for human pregnancy and fetal development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even within a normal birth -E-mail: mnsmit@ualberta.ca weight (BW) litter, intrauterine growth restriction (IUGR) and a low birth weight (LBW) can be characteristics of individual pigs (Wu et al, 2006). However, other studies suggested that IUGR can be a litter characteristic, driven by high ovulation rates and good to moderate early embryonic survival to day 30 of gestation in higher parity sows (Vonnahme et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Neonates born with IUGR have increased risk of postnatal morbidity and mortality, and IUGR is considered to be a major health concern worldwide for both humans and commercially raised domestic animals (Bateson et al, 2004;Wu et al, 2006). IUGR has been primarily attributed to placental insufficiency during the intrauterine phase (Wu et al, 2006), and can be regarded as the failure of a fetus to reach its genetic growth potential.…”
Section: Introductionmentioning
confidence: 99%